Facile intramolecular cyclization of N-(2 hydroxybenzoyl) hydrazones to N,N'-diacetyl benzo-1,3,4-oxadiazepine derivatives / Chan Pei Qie - Chan, Pei Qie (2018)
The synthesis of seven-membered benzo-1,3,4-oxadiazepines can be carried out through one-step intramolecular cyclization of N-(2-hydroxybenzoyl)hydrazones. The reaction was catalyzed by 4.50% (v/v) of sulfuric acid in acetic anhydride (Vt = 1 mL) at room temperature. The catalytic and substituent effects on the reactivity of this intramolecular cyclization were investigated. Through this strategy, a series of benzo-1,3,4-oxadiazepine derivatives were prepared (with yield up to 83%). These new heterocyclic compounds were characterized through their melting point, NMR and HRMS (ESI). It was observed that when electron-withdrawing group is at the para position of salicylic ring and electron-donating group at the para position of benzylidene ring, a good yield of seven-membered benzoxadiazepines were obtained. This strategy provided good method to a variety of substitution.